The Opinions Survey of People of Tax Collection of the Municipality Phitsanulok Municipality Mueang District Phitsanulok - Pengjan, Nontachai; RoJanatrakul, Tanastha (Journal of Humanities and Social Sciences, Rajapruk University, 2022)
The objectives of this research were 1) to study the level of local taxation of Phitsanulok City Municipality, Mueang District, Phitsanulok Province, 2) to compare the difference of personal factors with the local taxation of Phitsanulok City Municipality, Mueang District, Phitsanulok Province. The sample group to be used to represent the population is 400 people who pay taxes to Phitsanulok City Municipality. calculated by Taro Yamane’s formula at a 95% confidence level, this research tool is a questionnaire. the researcher chose to use statistics for data analysis. as follows: Descriptive statistics. by distributing it in terms of frequency, percentage, mean and standard deviation. Inferential statistics the statistics used in the test analysis are the t-test, and One-Way ANNOVA. The results of the study were as follows: 1) Respondents commented level of local taxation of Phitsanulok City Municipality, Mueang District, Phitsanulok Province overall, there is a considerable level of average 2) different personal factors, age, and education levels. the local taxation of Phitsanulok municipality, Muang District, Phitsanulok province, is statistically significant at .05.